On a dual role for clonidine stimulation of the ventromedial nucleus of the hypothalamus in sodium and potassium renal excretions of rats - Saad, Wilson Abrão [UNESP]; Camargo, Gabriela Pavan de Arruda [UNESP]; Camargo, Luiz Antonio de Arruda [UNESP] (Karger Publishers, 1996)
The effects of clonidine on sodium and potassium excretions were examined after previous administration of prazosin (an α 1-adrenergic receptor antagonist) and yohimbine (an α 2-adrenergic receptor antagonist) into the ventromedial nucleus of the hypothalamus of conscious rats. Clonidine injected into the ventromedial nucleus of the hypothalamus induced inhibitory and facilitatory effects on the urinary sodium and potassium excretions. The results suggest that facilitatory effects of clonidine on natriuresis and kaliuresis are mediated through activation of α 1-adrenoceptors and that inhibitory effects require α(2A)-adrenoceptors.
Keywords: Clonidine; Potassium excretion; Prazosin; Sodium excretion; Ventromedical nucleus, hypothalamus; Yohimbine; alpha 1 adrenergic receptor; alpha 2A adrenergic receptor; alpha adrenergic receptor stimulating agent; clonidine; potassium ion; prazosin; sodium ion; yohimbine; animal experiment; controlled study; intracerebral drug administration; kaliuresis; male; natriuresis; nonhuman; potassium urine level; priority journal; rat; sodium urine level; stimulation; thalamus ventral nucleus; Adrenergic alpha-Antagonists; Animals; Dose-Response Relationship, Drug; Hypothalamus; Kidney; Male; Potassium; Rats; Sodium